2012
DOI: 10.1016/j.juro.2011.10.158
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Extranodal Extension and Other Lymph Node Parameters in Patients With Upper Tract Urothelial Carcinoma

Abstract: Extranodal extension is a powerful predictor of clinical outcomes in patients with upper tract urothelial carcinoma with lymph node metastasis. While other lymph node parameters seem to have limited clinical value, extranodal extension could help risk stratify patients with upper tract urothelial carcinoma and lymph node metastasis for better counseling and clinical trial design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 22 publications
1
26
0
3
Order By: Relevance
“…These results support the diagnostic value of LND in patients with cN0 disease by finding microscopic metastasis. However, the reported incidence of LN metastasis is 16% in patients with muscle-invasive disease, while LN metastasis is rare in those with non-muscle-invasive disease, and the increased incidence is reportedly related to the pT stage (12,13). In our cohort, the incidence of LN metastasis was 18% in patients with cT2-4 disease but only 6% in patients with ≤cT1 disease.…”
Section: Discussionmentioning
confidence: 53%
“…These results support the diagnostic value of LND in patients with cN0 disease by finding microscopic metastasis. However, the reported incidence of LN metastasis is 16% in patients with muscle-invasive disease, while LN metastasis is rare in those with non-muscle-invasive disease, and the increased incidence is reportedly related to the pT stage (12,13). In our cohort, the incidence of LN metastasis was 18% in patients with cT2-4 disease but only 6% in patients with ≤cT1 disease.…”
Section: Discussionmentioning
confidence: 53%
“…Previously, a small series demonstrated that a LN density 30% was an independent predictor of higher cancer-specific mortality, 15 although this finding was not replicated in a follow-up study. 16 An alternate explanation for the association between the number of negative LNs and survival among pN0 patients is that a thorough LND can be truly therapeutic if it eradicates unidentified microscopic foci of metastatic disease that are missed on routine pathologic examination. This hypothesis is supported by a recent study that reported finding micrometastatic disease using immunohistochemistry in 14% of patients with UTUC who were initially classified as having pN0 disease but later presented with disease recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…La gestion de la collerette vésicale au cours de la NUT [55] ainsi que la zone anatomique de dissection du curage ganglionnaire associé [56,57] étaient des facteurs pronostiques impactant la survie des patients. Ils sont traités dans un autre chapitre du rapport de l'AFU consacré au traitement chirurgical des TVES.…”
Section: Facteurs Chirurgicauxunclassified